Impact Of Orientation On The Thermal Performance Of Building-Integrated Photovoltaic Modules In Ventilated Façades In Hot Climates (International Journal of Environmental Sciences, 2025)
Building-integrated photovoltaic (BIPV) systems represent a promising approach for creating a sustainable built environment by incorporating photovoltaic surfaces directly into the building envelope, effectively replacing conventional construction materials and building elements. These systems can be seamlessly integrated into a variety of components, including roofs, façades, windows, and shading devices. Among the various configurations, ventilated BIPV façades are increasingly recognized for their dual role in enhancing energy efficiency and generating clean energy. Despite their growing global relevance, the thermal performance of BIPV ventilated façades, particularly their heat loss factor (U), remains insufficiently explored in extremely hot climates, such as those in the Middle East. This work aims to identify the best-fit heat loss factor for simulating the energy yield of ventilated BIPV façades in Dubai. The factor was calibrated via one year of measurements from façades facing South, East, and West. The parametric simulations were conducted via PVsyst software. The analysis reveals that the heat loss factor is influenced not only by the mounting configuration but also by the orientation. The recommended thermal loss constant for semi-integrated solutions is 20 W/m2K. However, the best-fit values for the East, South, and West façades are 13, 17, and 27 W/m2K, respectively. With these values, the simulations exhibit excellent agreement with the measured energy yields, with the absolute difference and mean bias difference both below 0.3% and the root mean square difference under 5%. This study further validates the importance of calibrating the thermal parameters to the specific façade construction and climatic context, as it leads to enhanced simulation accuracy. Additionally, this study revealed that heat loss coefficients from PV modules in façades are influenced not only by wind and the free space behind them but also by the façade orientation.